Management of Breast Diseases - Jatoi, Ismail; Kaufmann, Manfred; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This multi-authored and comprehensive work provides a reference to the overall management of diseases of the breast (both benign and malignant). Pertinent controversies are discussed, and perspectives presented from both sides of the Atlantic. This highly practical guide serves as a reference for the wide range of physicians and surgeons who treat diseases of the breast.
Anatomy and Physiology of the Breast -- Congenital and Developmental Abnormalities of the Breast -- Nipple Discharge -- Mastalgia -- Management of Common Lactation and Breastfeeding Problems -- Evaluation of a Breast Mass -- Breast Cancer Epidemiology -- Breast Cancer Screening -- Breast Imaging -- Premalignant and Malignant Breast Pathology -- Lobular Carcinoma in Situ -- Ductal Carcinoma in Situ -- Surgical Considerations in the Management of Primary Invasive Breast Cancer -- Sentinel Node Concept -- Breast Reconstructive Surgery -- The Role of Radiotherapy in Breast Cancer Management -- Adjuvant Systemic Therapy for Breast Cancer: An Overview -- Endocrine Therapy -- Chemotherapeutic Agents -- HER2-Targeted Therapy -- Inflammatory and Locally Advanced Breast Cancer -- Preoperative (Neoadjuvant) Systemic Therapy -- Metastatic Breast Cancer -- Hormone Replacement Therapy: A Critical Review -- Breast Diseases in Males -- Breast Cancer in the Elderly -- Breast Cancer in Younger Women -- Psychological Support for the Breast Cancer Patient -- Management of the Patient with a Genetic Predisposition for Breast Cancer -- Chemoprevention of Breast Cancer -- Design, Implementation, and Interpretation of Clinical Trials -- Structure of Breast Care Center -- Medicolegal Pitfalls in Breast Cancer Diagnosis and Management.
Keywords: Medicine; Gynecology; Radiology, Medical; Internal medicine; Cancer -- Surgery; Surgery; Medicine & Public Health; Surgery; Surgical Oncology; Gynecology; Imaging / Radiology; Internal Medicine